Application of artificial intelligence technologies in criminal proceedings: realities and prospects - Krushynskyi , Serhii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2025)
The article analyses certain problems that arise in the process of applying artificial intelligence technologies in criminal proceedings. It is stated that different states are at different stages of integrating artificial intelligence technologies into criminal proceedings. The example of China is given as an absolute leader in this process, which has introduced a system of «smart courts» (Smart Court SoS). At the same time, a much more cautious approach of European states is demonstrated, it focused primarily on compliance with the principles of the rule of law, non-discrimination, independence and impartiality of the judiciary, the right to a fair trial, the right to privacy and protection of personal data, the right to freedom of expression, etc. It is concluded that the integration of AI technologies into criminal proceedings can potentially improve the quality, efficiency and effectiveness of judicial proceedings, but provided that a number of risks of a technical, legal and ethical nature are eliminated. One of the unresolved problems today remains the ability of artificial intelligence systems to create fake legal facts or norms that look plausible (so-called «legal hallucinations»). At the same time, significant potential for the use of AI technologies exists at the stage of pre-trial investigation, in particular, for the rapid processing of large databases and information arrays and the performance of identification tasks (recognition of faces, voices, fingerprints, license plates, etc.). The regulatory acts on the possibility of introducing and using artificial intelligence in criminal proceedings in Ukraine are analysed. In particular, justice is attributed to the priority areas in which the tasks of the state policy for the development of the field of artificial intelligence are implemented.